Quantity Take-off Using Building Information Modeling on Superstructure Works - Farhan Rafid Bahtiar; Siti Nurasiyah; Istiqomah Istiqomah (Portal: Jurnal Teknik Sipil, 2025)
Technological advancements in the construction industry have encouraged the adoption of Building Information Modeling (BIM) as a digital approach in project implementation. This study discusses the implementation of BIM in calculating work volumes (Quantity Takeoff/QTO) and project scheduling by considering labor fluctuations through resource leveling analysis. The objective of this research is to compare QTO results between BIM and conventional methods, as well as to analyze labor requirements and project duration. This research uses a case study method on the superstructure phase of a building project. The comparison results show a difference in work volumes between the BIM and conventional methods, namely 8.98% for reinforcement work, 13.23% for concrete casting, and 8.57% for formwork. Based on these findings, this study provides a quantitative overview of the differences between the conventional and BIM-based methods in terms of work volume. Further studies are recommended using more diverse case objects and a broader scope of construction work.